Treatment beyond progression in non-small cell lung cancer: A systematic review and meta-analysis - Kuo, Wei-Ke; Weng, Ching-Fu; Lien, Yin-Ju (Frontiers in Oncology, 2022)
Objectives: Treatment beyond progression (TBP) is defined as treatment continuing in spite of disease progression, according to the Response Evaluation Criteria In Solid Tumors. We performed a systematic review and meta-analysis to provide evidence for the effects of TBP on lung cancer survival. Materials and methods: This study has been conducted following the PRISMA guidelines. A systematic review of PubMed, MEDLINE, Embase, and Cochrane Collaboration Central Register of Controlled Clinical Trials from the inception of each database to December 2021 was conducted. Two authors independently reviewed articles for inclusion and extract data from all the retrieved articles. Random-effects meta-analysis was performed using Comprehensive Meta-Analysis software, version 3 (Biostat, Englewood, NJ, USA). Hazard ratios (HRs) with the corresponding 95% confidence intervals (CI) were used for survival outcomes. Results: We identified five (15.6%) prospective randomized trials and twenty-seven (84.4%) retrospective observational studies of a total of 9,631 patients for the meta-analysis. 3,941 patients (40.9%) were in a TBP group and 5,690 patients (59.1%) were in a non-TBP group. There is a statistically significant advantage for patients who received TBP compared with those who did not in post progression progression-free survival (ppPFS), post progression overall survival (ppOS), and overall survival (OS) from initiation of drugs (ppPFS: HR, 0.746; 95% CI, 0.644-0.865; P<0.001; ppOS: HR, 0.689; 95% CI, 0.596-0.797; P<0.001; OS from initiation of drugs: HR, 0.515; 95% CI, 0.387-0.685; P<0.001) Conclusion: This study provides further evidence in support of TBP for NSCLC, however, these results require cautious interpretation. Large, randomized, controlled trials investigating the efficacy of TBP in lung cancer treatment are warranted.